Muslim revert narrative and American gaze post 9/11 in Jamilah Kolocotronis' Rebounding - Hassan Majid Ahmed,; Raihanah M. M.,; Ruzy Suliza Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper focuses on the manifestations of the American gaze post-9/11 as portrayed in the fictional narrative, Rebounding, by Jamilah Kolocotronis. Kolocotronis, a Caucasian American Muslim revert whose novels in the Echoes Series highlight the American Muslim revert’s personal, interpersonal and multicultural complexities of living in post-9/11 America. Those complexities are made obvious through the American gaze post-9/11 as intentional views, behaviors and actions made by certain members of the non-Muslim American majority towards white and non-white Muslims minority, due to affiliation with Islam. By using the post-9/11 counterterrorism perspective on national security, this article problematises the American gaze post-9/11 by explicating how the protagonist Joshua Adams’ material support to a Muslim fellow in Pakistan has brought serious repercussions on his personal and public life. Efforts are also devoted to delineate the transition of the American gaze post-9/11 from the private level, i.e., Joshua’s clash with his father Sam, to the public level, through Joshua’s incarceration by the Homeland Security agents. The findings reveal that the American post- 9/11 gaze move beyond the realm of race and nationality into the space of religiosity. It positions Joshua in the grip of atonality, robbing him of his faith, selfhood, and citizenship on both private and public levels. Kolocotronis’ Rebounding expounds how the severity of the post-9/11 American gaze fails to fully establish a sharp distinction between innocent Americans and terrorists. An essential feature of civic engagement which is neglected in post-9/11America as illustrated in this novel is the recognition of the American Muslim revert's public service, virtues and achievements, which demonstrates the premises of separation and association with forces of terrorism.